Acoustic excitation on flame properties caused by two sound sources - Samsubaha, Muhammad Fauzi (2020)
Research and development in understanding the responses of acoustic excitation as a meant to influence flame behavior have become one of the significant issues in combustion instability. This interaction can be found in most processing, power generating, and propulsion application. Some of the responses that can be seen from the interaction are lift-off phenomenon, changes of flame macroscopic structure, and production of emission that contribute to the environment. However, it seems there are insufficient data that were focusing mainly on the change of flame properties and how it's being affected by the increase of acoustic excitation. The need to publish some of the significant results and helps improve the understanding of combustion instabilities became the major motivational in conducting the research. This study adopted experimental research and understanding the change of flame behavior by differentiates two number of speakers (source of acoustic) excited to the flame. For data collection, it employs a direct imaging technique using a DSLR camera. The data obtained were analyzed using image processing software, Image J. This experiment focuses on the change of flame properties based on the number of the speaker (source of acoustic) used with the increased number of frequencies. The flame shape obtain in this experiment is divided into disturbances and un-disturbance categories, and each shape is then thoroughly discussed by focusing on the change of its length, width, and angle. The results from this experiment shows that the response of flame is significantly affected by the configuration of speakers (sound source) and the magnitude of amplitude used. It indicated that for dual speakers and higher amplitude in terms of its flame characteristic shows a promising flame response compare with a single speaker and lower amplitude